The Potential of Pasak Bumi (Eurycoma longifolia Jack) Root Extract Nanoparticles as Anti-Prostate Cancer Agent against Cell Cycle Regulation, Apoptosis, and Senescence based on In Vitro Tests - Eka Yudha Rahman; Nia Kania; Didik Priyandoko; Adilah Hafizha Nur Sabrina; Wahyu Widowati; Rizal Azis; Aziz Annaba; Dhanar Septyawan Hadiprasetyo; Garry Alexandro (Journal of Mathematical and Fundamental Sciences, 2026)
Prostate cancer poses a major health challenge worldwide, with increasing incidence rates and limited current treatment modalities, which highlights the urgent need for innovative therapeutic alternatives. Utilizing nanoparticles derived from plant extracts is emerging as a promising solution, offering a superior drug delivery system. Eurycoma longifolia Jack roots, or Pasak Bumi, which are widely used in ethnobotany, are known to contain the compound eurycomanone, which exhibits pro-apoptotic activity against malignant cells. This investigation sought to assess the efficacy of Pasak Bumi root-derived nanoparticles (PBN) in inhibiting the proliferation of prostate carcinoma cells (PC-3), through an in vitro approach. A nanoparticle sample was obtained through the addition of chitosan and 0.4% Na-TPP to Pasak Bumi root extract. Flow cytometric analysis was employed to evaluate cell cycle distribution, while genes expression of Casp-3, Casp-8, and HAX-1 were quantified via qRT-PCR. The senescence cell detection test was performed using associated-β-galactosidase staining. PBN treatment supressed PC-3 cell proliferation through G0/G1 phase arrest and downregulation of HAX-1 genes expression, while promoting apoptosis via upregulation of Casp-3 and Casp-8 transcripts. PBN also increased the percentage of PC-3 senescence cells. This study demonstrates the potential of PBN to inhibit prostate cancer cells.